Cloning of the Rhodobacter capsulatus hemA gene. - Biel, S W (1988)
Portions of the Rhodobacter capsulatus hemA gene have been cloned from a hemA::Tn5 insertion strain into the lambda bacteriophage derivative EMBL3. A cosmid containing the wild-type R. capsulatus hemA gene was isolated by complementation of the hemA::Tn5 mutant. The cosmid contains a 1.4-kilobase EcoRI fragment that spans the hemA::Tn5 insertion site. The entire hemA gene is contained in this fragment and the adjacent 0.6-kilobase EcoRI fragment.